Clinical, morphogical and immunohistochemical aspects of oral inflammatory myofibroblastic tumor: a rare case report in a pediatric patient - Santos, Hellen Bandeira de Pontes; Barbosa, Natália Guimarães; Silva Filho, Tiago João; Queiroz, Lélia Maria Guedes; Gurgel, Alberto; Freitas, Roseana de Almeida; Oliveira, Patrícia Teixeira de (ARCHIVES OF HEALTH INVESTIGATION, 2018)
Inflammatory myofibroblastic tumor (IMT) is a rare benign neoplasm composed by myofibroblasts and fibroblasts admixed with inflammatory cells. Here, we report a case of IMT in the oral cavity of left mandible of a 12-year-old boy. Histopathological investigation revealed a proliferation of fibroblasts and myofibroblasts (positive for alpha-smooth muscle actin and vimentin) associated with inflammatory cells. The patient is still under follow-up and without evidence of recurrence. Oral IMT is a challenge for the clinician in diagnosis due to the nonspecific clinical presentation. Thus, histology and immunohistochemistry are required to reach an accurate diagnosis of this lesion. Descriptors: Neoplasms; Diagnosis; Immunohistochemistry.